2014
DOI: 10.1097/mph.0000000000000077
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine Arabinoside and Mitoxantrone Followed by Second Allogeneic Transplant for the Treatment of Children With Refractory Juvenile Myelomonocytic Leukemia

Abstract: Summary Hematopoietic stem cell transplantation (HSCT) remains the only curative option for most patients with juvenile myelomonocytic leukemia (JMML). However, persistent disease and relapse rates after transplant range from 26% to 58%. We report the successful use of second HSCT after preparation with mitoxantrone and cytosine arabinoside (Ara-C) for patients with refractory or recurrent disease. Between 1993 and 2006, 5 children who underwent HSCT at our institution as initial therapy for JMML had persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…(1, 2, 915) Studies of second transplant in children have demonstrated more favorable survival, but are limited by small patient numbers. (11, 16) Previous studies of second transplant have been limited in sample size and hence, have been inconsistent in identifying favorable factors for longer survival following second allogeneic HCT. Notwithstanding the limitation of small sample size, factors associated with superior survival include younger recipient age, longer duration of remission between transplants, complete remission (CR) at second transplant, bone marrow as the stem cell source, the use of a fully HLA-matched donor, the presence of acute and chronic graft-versus-host disease (GVHD), and transplantation from a female donor.…”
Section: Introductionmentioning
confidence: 99%
“…(1, 2, 915) Studies of second transplant in children have demonstrated more favorable survival, but are limited by small patient numbers. (11, 16) Previous studies of second transplant have been limited in sample size and hence, have been inconsistent in identifying favorable factors for longer survival following second allogeneic HCT. Notwithstanding the limitation of small sample size, factors associated with superior survival include younger recipient age, longer duration of remission between transplants, complete remission (CR) at second transplant, bone marrow as the stem cell source, the use of a fully HLA-matched donor, the presence of acute and chronic graft-versus-host disease (GVHD), and transplantation from a female donor.…”
Section: Introductionmentioning
confidence: 99%
“…In the present era, with several advances in posttransplantation supportive care practices, it is not unusual for a second allogeneic HSCT to be a considered as treatment for patients whose disease relapse after first HSCT; however, few reports had been published focusing its efficacy and safety . Our current study is one of the largest reports in the pediatric population and demonstrated that more than 40% of the children can be cured following a second HSCT and second remission.…”
Section: Discussionmentioning
confidence: 65%
“…a second allogeneic HSCT to be a considered as treatment for patients whose disease relapse after first HSCT; however, few reports had been published focusing its efficacy and safety. [2][3][4][5][6][7][8] Our current study is one of the largest reports in the pediatric population and demonstrated that more than 40% of the children can be cured following a second HSCT and second remission. A major concern of HSCT for the second time is the potentially high risk of transplant-related toxicity, and indeed, an extremely high rate of transplant-related mortalities (TRM) was the major cause of treatment failure in the previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations